A Mixed Methods Study on the Status of School Orchestra Programs in Oregon: An Explanation of Inhibiting and Promoting Factors. Issue 1 (July 2019) - Ihas, Dijana
The purpose of this explanatory sequential mixed methods study was to examine the status of school orchestra programs in Oregon and to explain the reasoning behind the descriptive data. The quantitative phase of the study reported the data on the number of school districts and schools by type that offer orchestra instruction as well as the profile of those schools, their orchestra programs, and orchestra teachers. Unexpected findings from the quantitative phase indicated that among the three large school districts that are comparable in size, budget, and students' demographics, only one offers orchestra instruction in every school within the district ( n = 65) while the other two districts offer orchestra instruction in one high school each. This finding prompted the qualitative phase of the study that illuminated factors that inhibit and promote the quality of education within Oregon schools. The mixed methods findings explained the discrepancy in music offerings among the three large school districts through the perspectives of the three arts administrators, one from each district.